2018
DOI: 10.1159/000486624
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Dexamethasone on Regorafenib-Related Fatigue and/or Malaise: A Randomized, Placebo-Controlled, Double-Blind Clinical Study in Patients with Unresectable Metastatic Colorectal Cancer (KSCC1402/HGCSG1402)

Abstract: Background: Regorafenib is an oral multikinase inhibitor with a proven survival benefit for metastatic colorectal cancer patients. The KSCC1402/HGCSG1402 study investigated the prophylactic effect of oral dexamethasone (DEX) on regorafenib-related fatigue and/or malaise. Patients and Methods: Patients who progressed after standard chemotherapy were randomized 1: 1 to a DEX group (2 mg/day; days 1–28) with regorafenib or a placebo group with regorafenib. The primary endpoint was the incidence of fatigue and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The result from this review showed that methylphenidate and corticosteroids may improve CRF in the palliative phase [14,34,35,39,46,48] but there is not enough evidence to propose use of modafinil, dexamphetamine, melatonin or testosterone in this setting. It should be noted that the studied cohorts are heterogeneous and include patients both in the early and late palliative phase.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The result from this review showed that methylphenidate and corticosteroids may improve CRF in the palliative phase [14,34,35,39,46,48] but there is not enough evidence to propose use of modafinil, dexamphetamine, melatonin or testosterone in this setting. It should be noted that the studied cohorts are heterogeneous and include patients both in the early and late palliative phase.…”
Section: Discussionmentioning
confidence: 92%
“…Meta-analyses and group comparisons are therefore of little use at present, and instead we suggest that each study should be evaluated individually regarding generalizability of results. Unfortunately, characterization of disease severity in patients included in several studies in this review is scarce, and survival time is only accounted for in two trials [14,33]. Instead, inclusion and exclusion criteria, description of care facilities from which patients were recruited, assessed performance status at baseline and data on dropout rates and reasons for not completing intervention can be used to estimate general disease burden in studied cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, for treatment-related fatigue, one phase II study investigated the effect of dexamethasone on these patients but failed to show any improvement. 10 Currently there is no established marker to predict the treatment response towards regorafenib. In our study, patients with left-sided tumours enjoyed longer OS, which concurs with the findings of many other studies that left-sided tumours carry a better prognosis regardless of treatment, stage, race of patients, or length of study.…”
Section: Discussionmentioning
confidence: 99%